The Roles of Gray Divorce and Subsequent Repartnering for Parent–Adult Child Relationships. (26th July 2021) - Lin, I-Fen; Brown, Susan L; Mellencamp, Kagan A
Abstract: Objectives: Divorce is now widespread in later life, yet little is known about how older adults and their adult children respond in the aftermath of gray divorce. Guided by the life course perspective, this study examines the consequences of gray divorce and subsequent repartnering for parent–adult child relationships from the parent's perspective. Methods: Using longitudinal data from the 1998–2014 Health and Retirement Study in the United States, we estimated growth curve models to compare fathers' and mothers' frequent contact with and financial support to their adult children prior to, during, and following gray divorce. Results: Gray divorce and repartnering had disparate effects on father– versus mother–adult child relationships. Following a divorce, fathers' frequent contact with their adult children decreased but financial support to their adult children increased. Fathers' repartnering had an enduring negative effect on frequent contact with their children. Gray divorce did not alter mothers' financial support to adult children and it actually increased interaction between mothers and adult children as the odds of frequent contact doubled upon divorce. Repartnering had no appreciable effects on mothers' relationships with their adult children. Discussion: The results of our study are consistent with prior research showing that divorce creates a matrifocal tilt in our kinship system. The shifting dynamics of parent–adult child relationships in response to gray divorce and repartnering raise questions about whether gray-divorced parents will be able to rely on their adult children for care as they age.